Real contact area characteristics on the micro scale - Brodnik Žugelj, Blaž (visokošolska dela, 2017)
In conventional engineering approach, contact conditions are calculated with the assumption of nominal contact area between two surfaces, which is greater than actual contact area. Consideration of such assumptions leads into calculations of milder contact conditions as they appear in real. In this PhD thesis we investigated the influence of engineering-relevant material and topographic properties on the actual behaviour within the contact of two nominally flat surfaces under static loading conditions. For this purpose, a novel test rig was developed, which enables the analysis of the contact on a submicron scale. The results showed that at the macro yield stress metals exhibit similar contact behaviour, while the influence of topographic properties is more prominent. On the contrary, polymer shows different contact behaviour than metals. In-depth experimental analysis of asperity deformations showed that the contact behaviour is strongly affected by the material and topographic changes of the contacting asperities. The obtained experimental results were compared to the predictions of well-established theoretical contact models. Due to the assumptions of theoretical contact models, large deviations between the predicted and actual contact behaviour were observed.
Keywords: asperity deformations; contact of two nominally flat surfaces; deformacija vršičkov; Disertacije; dissertations; eksperimentalna in-situ analiza; experimental in-situ analysis; kontakt ravnih površin; Kontaktne površine; material properties Surface topography; materialne lastnosti; real contact area; realna kontaktna površina; topografija površin